2014
DOI: 10.1515/ap-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Risk of human toxocarosis in Poland due to Toxocara infection of dogs and cats

Abstract: The purpose of this paper was to present the current data on the risk of toxocarosis in humans in Poland and to give an overview of the clinical and diagnostic aspects of the disease. The number of reported clinical cases of Toxocara infection in children in Poland in medical literature has increased recently. The results of field surveys aimed to evaluate the soil contamination with geohelminth eggs conducted during the last few years showed that Toxocara is the most common zoonotic agent in urban public site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…However, exposure to Toxocara eggs is much higher than to other geohelminths, as evidenced by the large number of reports from many parts of the world (Magnaval et al 2001;Gawor et al 2015). Also in this study we found Toxocara spp.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, exposure to Toxocara eggs is much higher than to other geohelminths, as evidenced by the large number of reports from many parts of the world (Magnaval et al 2001;Gawor et al 2015). Also in this study we found Toxocara spp.…”
Section: Discussionsupporting
confidence: 59%
“…The high prevalence of the infection together with the high fecundity of the roundworm and the increasing number of pet animals explain the elevated level of soil contamination with Toxocara eggs in public and private places (Gawor et al , 2015. Human exposure to the infective stages (embryonated eggs) is high, and the risk of infection is noticeably increased by the fact that the eggs survive in the environment for several years.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the municipal authorities must, by March 31st, adopt an annual program for the care of homeless animals and the prevention The authors of the publication draw attention to the diversity of threats, not only between countries and cities, but even between nearby areas. 3,5,7,17,19,30,31,33,37,44 In the light of the above, changes to the Polish law in the field of public health protection, which have occurred in recent years, are very questionable. The removal of diseases with dangerous and irreversible effects to human health and life from the list of infectious diseases defies logical explanation.…”
Section: Resultsmentioning
confidence: 99%
“…This is despite many reports indicating the need for monitoring the dangers for people, especially children, coming from the animals constituting the links of the epidemiological chain. 30 state the constant risk of human contact with factors causing both diseases. 1,3,4,8,14,18,30,31,38,53 Despite difficulties in diagnosing toxoplasmosis and toxocarosis in humans sanitary services, without keeping records of these diseases and without knowing local threats, cannot take preventive action.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation